Sirtuin 1 in skeletal muscle of cachectic tumour-bearing rats: a role in impaired regeneration? - Toledo, Míriam (Springer-Verlag, 2011)
BACKGROUND: In advanced malignant disease, cachexia and muscle wasting appear to be among the most common manifestations. This phenomenon is partially related with a decreased muscle regeneration capacity, as previously described in our laboratory. METHODS AND RESULTS: Rats bearing the Yoshida AH-130 ascites hepatoma were used in the experiments. The animals experienced a marked weight loss with decreases in skeletal muscle weights (13% gastrocnemius, 18% extensor digitorum longus, and 12% tibialis muscles). Muscle gene expression was measured using real-time polymerase chain reaction. Skeletal muscle from cachectic tumour-bearing rats is associated with a decreased expression of genes involved in regeneration such as Pax-7 (39%), myogenin (24%), and MyoD (17%). mRNA levels of Sirt1 increased (91%) in cachectic skeletal muscle. The Sirt1 gene has been shown to be associated with changes in muscle myoblast differentiation. Treatment of the tumour-bearing animals with formoterol—a beta2-agonist—normalizes the expression of genes involved in regeneration (i.e., increase of Pax7 (139%)), at the same time as it does with that of Sirt1 (42% decrease). CONCLUSIONS: It is suggested that the lack of muscle regeneration observed during muscle wasting in tumour-bearing animals is linked to the action of Sirt-1, possibly via PGC-1α. These factors may constitute possible targets of pharmacological treatment against muscle loss, thus potentially contributing to the understanding and mitigation of muscle atrophy associated with disease.